2022
DOI: 10.1037/law0000342
|View full text |Cite
|
Sign up to set email alerts
|

Guiding jurors’ damage award decisions: Experimental investigations of approaches based on theory and practice.

Abstract: Theory and practitioner “scaling” advice informed hypotheses that guidance to mock jurors should (a) increase validity (vertical equity), decrease variability (reliability), and improve coherence in awards; (b) improve subjective experience of jurors’ decision-making (rated helpfulness, confidence, and difficulty); and (c) have the greatest impact when it includes both verbal and numerical benchmarks. Three mock juror experiments (N = 197 students, N = 476 Amazon Mechanical Turk workers, and N = 391 students) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 47 publications
4
12
0
Order By: Relevance
“…Laypeople showed substantial uncertainty about the precise amount of these sanctions to impose, as reflected in Figure 4, with values stretching many orders of magnitude. This finding is consistent with research into jury damage awards for emotional damages, which show substantial variance unless guided by anchors and instructions (Hans et al, 2022). However, lay participants broadly agreed that the value should be above zero, which is where the quantities imposed in real sentences cluster.…”
Section: Discussionsupporting
confidence: 89%
“…Laypeople showed substantial uncertainty about the precise amount of these sanctions to impose, as reflected in Figure 4, with values stretching many orders of magnitude. This finding is consistent with research into jury damage awards for emotional damages, which show substantial variance unless guided by anchors and instructions (Hans et al, 2022). However, lay participants broadly agreed that the value should be above zero, which is where the quantities imposed in real sentences cluster.…”
Section: Discussionsupporting
confidence: 89%
“…These results suggest that it is the gist of information on prevalence, rather than verbatim information (precise prevalence estimates) that is relied on and reflected in legal lie detection judgements (although absent interference gist judgements are likely to correspond well to verbatim judgements; see Hans et al, 2022). In fact, while changing gists influenced judgements (discussed above), exploratory analyses showed that relationships between precise prevalence estimates and lie detector judgements were nonsignificant where information on prevalence framed to emphasize a particular gist was given.…”
Section: Discussionmentioning
confidence: 94%
“…Gist extracted from information often corresponds with verbatim information (e.g., a higher verbatim number is more likely to be encoded as “high” than a lower verbatim number; see Hans et al, 2022). As a result, errors in verbatim representations are likely to correspond with inappropriately assigned gist (gist assigned based on misunderstanding).…”
Section: Study 2: Manipulating Perceptions Of Prevalence and Legal Li...mentioning
confidence: 99%
“…Prior research focused on assisting jurors in translating their qualitative gist into a quantitative award for the case as a whole. In other words, both the anchor provided by the foreperson (Hans et al, 2018; Reyna et al, 2015) and the scaling guidance (Hans et al, 2022) had jurors focus on the value of the whole case. However, research on numerical cognition suggests that people struggle with discriminating among large numbers (Landy et al, 2013; Reyna & Brainerd, 2023).…”
Section: Normative Benchmarksmentioning
confidence: 99%